Political Aspects of Health Care Navigating the Waters of Conflicting Policy - Lavanty, Donald F. (Palgrave Macmillan US, 2018)
As a consultant for healthcare associations working on all the healthcare laws from Medicare, the Health Manpower Act, Budget Reconciliation, Clinton healthcare efforts and the Affordable Healthcare Act, Donald Lavanty had a front-row seat from which to witness the politics and policies motivating each action. This volume was written from that experience, which was first documented in the course on the Political Aspects of Healthcare, employing the analogy that these various legislative actions to connect the system are like attempting to build a canal connecting the Amazon and Nile rivers: a long and difficult process. The title examines ongoing efforts to create and maintain a workable solution to the conflicts inherent in the US healthcare system from all angles, conflicts that arise due to the nature of our democratic government in which healthcare policies change based on the position of the voting majority in Congress at the time any action is taken. .